A glimpse on the pattern of rodent diversification: a phylogenetic approach - Fabre, Pierre-Henri; Hautier, Lionel; Dimitrov, Dimitar; P Douzery, Emmanuel J (BMC evolutionary biology, 2012)
Development of phylogenetic methods that do not rely on fossils for the study of evolutionary processes through time have revolutionized the field of evolutionary biology and resulted in an unprecedented expansion of our knowledge about the tree of life. These methods have helped to shed light on the macroevolution of many taxonomic groups such as the placentals (Mammalia). However, despite the increase of studies addressing the diversification patterns of organisms, no synthesis has addressed the case of the most diversified mammalian clade: the Rodentia. Here we present a rodent maximum likelihood phylogeny inferred from a molecular supermatrix. It is based on 11 mitochondrial and nuclear genes that covers 1,265 species, i.e., respectively 56% and 81% of the known specific and generic rodent diversity. The inferred topology recovered all Rodentia clades proposed by recent molecular works. A relaxed molecular clock dating approach provided a time framework for speciation events. We found that the Myomorpha clade shows a greater degree of variation in diversification rates than Sciuroidea, Caviomorpha, Castorimorpha and Anomaluromorpha. We identified a number of shifts in diversification rates within the major clades: two in Castorimorpha, three in Ctenohystrica, 6 within the squirrel-related clade and 24 in the Myomorpha clade. The majority of these shifts occurred within the most recent familial rodent radiations: the Cricetidae and Muridae clades. Using the topological imbalances and the time line we discuss the potential role of different diversification factors that might have shaped the rodents radiation. The present glimpse on the diversification pattern of rodents can be used for further comparative meta-analyses. Muroid lineages have a greater degree of variation in their diversification rates than any other rodent group. Different topological signatures suggest distinct diversification processes among rodent lineages. In particular, Muroidea and Sciuroidea display widespread distribution and have undergone evolutionary and adaptive radiation on most of the continents. Our results show that rodents experienced shifts in diversification rate regularly through the Tertiary, but at different periods for each clade. A comparison between the rodent fossil record and our results suggest that extinction led to the loss of diversification signal for most of the Paleogene nodes.